The relationship between the nutrient supply and the yield of maize hybrids with different genetic traits on chernozem soil in variant years - Egriné Becze, Zsófia; Sárvári, Mihály (Acta Agraria Debreceniensis, 2015)
The experiments were set on lime-coated chernozem soil in 2013 and in 2014, in our study four hybrids were included with different FAO number. We studied the effect of NPK fertilization and row spacing on the yield. The fertilizer doses were based on a 25-year longterm experiment. Compared to control, the N40 +PK treatment has also achieved a significant yield increase, although some hybrids responsed with yield loss to the increasing fertilizer doses; this effect was observed especially in 2014. The majority of hybrids reached higher yields in both years using the 50 cm row spacing. The water release of hybrids was measured weekly during the maturation, at the same time points. The rainy September slowed ripening and the water release of the hybrids in 2013, so the grain wet content at harvest showed higher values. The moisture contents were increased for some hybrids, in spite of the positive and favorable dynamic of water loss.